Housing and Health among Young First Nations Children Living Off Reserve: Results from the 2006 Aboriginal Children’s Survey - Anne Guevremont; Evelyne Bougie; Dafna Kohen (aboriginal policy studies, 2016)
First Nations children in Canada often experience poorer housing conditions than other Canadian children. This study used the 2006 Aboriginal Children’s Survey to examine the relationship between housing and physical and mental health for First Nations preschool-aged children living off-reserve. This study provides evidence that the physical, spatial, and psychological aspects of housing in which young off-reserve First Nations children live are associated with their physical and mental health, even after controlling for family socioeconomic factors, area of residence, and child’s age and sex (analyzed with regression models). In particular, homeownership, parental satisfaction with housing, and number of moves per year were all associated with multiple physical and mental health outcomes. Future research is needed to further investigate the mechanisms at play.